Resistive switching device based on high-mobility graphene and its switching mechanism. Issue 2 (February 2019) - Zhang, Enliang; Zhou, Quan; Shen, Jun
Abstract: Graphene is a promising material for fast memory device, due to its high mobility and potential for ultrasmall linewidth. However, the high mobility are normally obtained with strict limitations, such as Boron nitride substrate and capping layer, or low temperature with mechanical exfoliation. In this paper, we modified the fabrication process of graphene device, and high carrier mobility larger than 10, 000 cm 2 /(Vs) was obtained for graphene grown by chemical vapor deposition. Resistive switching devices based on these high mobility graphene were fabricated, and the conducting mechanism of the switching process were discussed in detail. A model based on a Schottky diode in series connection with a tunneling junction is found to be consistent with the conducting mechanism. Our results are useful for normal research groups with only traditional nanofabrication facility.